DNA Barcoding of Medicinal Orchid Dendrobium discolor Lindl. Tanimbar Using rbcL and ITS genes - Dian Al Ghifari Perwitasari; Siti Rohimah; Tri Ratnasari; Bambang Sugiharto; Mukhamad Su'udi (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Dendrobium discolor Lindl., Tanimbar is one of the medicinal orchids that has been used to treat skin diseases. Morphologically, D. discolor Tanimbar shows similarities with D. discolor Merauke and D. bigibbum, making it challenging to identify. DNA barcoding using ribulose-1,5-bisphosphate carboxylase large (rbcL) and Internal Transcribed Spacer (ITS) markers expected to be used to identify D. discolor accurately. This study aimed to identify potential DNA sequences as barcodes for the identification of medicinal orchid D. discolor Tanimbar using molecular markers rbcL and ITS. The DNA genome of D. discolor Tanimbar was isolated and used as a template in the PCR reaction. The resulting amplicons were then sequenced. The results showed that the rbcL gene sequence of D. discolor had high homology with D. salaccense (Accession: LC193510.1, Prect. Ident : 99.45 %), whereas the ITS had high homology with D. nindii (Accession: AY239985.1 Identification: 98.67 %). Bioinformatics analysis showed that the rbcL gene sequence from D. discolor had more homology sequence than the ITS. However, the ITS sequence was more specific and could differentiate to species level. Based on the results of this study, the ITS sequence can be recommended as a molecular marker for the identification of the medicinal orchid D. discolor Tanimbar.